NLRP7 in the spectrum of reproductive wastage: rare non-synonymous variants confer genetic susceptibility to recurrent reproductive wastage. Issue 8 (9th June 2011) - Messaed, Christiane; Chebaro, Wafaa; Roberto, Raphael B Di; Rittore, Cecile; Cheung, Annie; Arseneau, Jocelyne; Schneider, Ariel; Chen, Moy Fong; Bernishke, Kurt; Surti, Urvashi; Hoffner, Lori; Sauthier, Philippe; et al.
Abstract : Background: NLRP7 mutations are responsible for recurrent molar pregnancies and associated reproductive wastage. To investigate the role of NLRP7 in sporadic moles and other forms of reproductive wastage, the authors sequenced this gene in a cohort of 135 patients with at least one hydatidiform mole or three spontaneous abortions; 115 of these were new patients. Methods/Results: All mutations were reviewed and their number, nature and locations correlated with the reproductive outcomes of the patients and histopathology of their products of conception. The presence of NLRP7 mutations was demonstrated in two patients with recurrent spontaneous abortions, and some rare non-synonymous variants (NSVs), present in the general population, were found to be associated with recurrent reproductive wastage. These rare NSVs were shown to be associated with lower secretion of interleukin 1β and tumour necrosis factor and therefore to have functional consequences similar to those seen in cells from patients with NLRP7 mutations. The authors also attempted to elucidate the cause of stillbirths observed in 13% of the patients with NLRP7 mutations by examining available placentas of the stillborn babies and live births from patients with mutations or rare NSVs. A number of severe to mild placental abnormalities were found, all of which are known risk factors for perinatal morbidity. Conclusions: The authors recommend close follow-up of patients with NLRP7 mutations and rare NSVs to prevent the death of the rare or reduced number of babies that reach term.